2021
DOI: 10.1108/nfs-06-2021-0172
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial glycemic response in different bakery formulations with adequate palatability: sex-related effects

Abstract: Purpose Hyperglycemic diets are a critical risk factor for diabetes and other chronic diseases; therefore, food innovation is encouraged. In this sense, starchy foods with a better postprandial glycemic response (PGR) could contribute to disease prevention for consumers. This study aims to evaluate the effect of three biscuit formulations on glycemic indicators – in general, and by sex – and their acceptability. Design/methodology/approach The authors analyzed the nutritional composition of biscuits A, B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported sex-specific differences in postprandial glycemic response to various meal treatments. Niclis et al reported that women exhibited a lower postprandial glycemic response than men after consuming all variations of biscuits that varied in nutrient content [ 23 ]. Ahmed et al reported a lower postprandial glucose peak in women compared to men, especially after breakfast [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported sex-specific differences in postprandial glycemic response to various meal treatments. Niclis et al reported that women exhibited a lower postprandial glycemic response than men after consuming all variations of biscuits that varied in nutrient content [ 23 ]. Ahmed et al reported a lower postprandial glucose peak in women compared to men, especially after breakfast [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared the postprandial glycemic response in 20 young, healthy college students (12 female, 8 male), after consuming whole fruit (apple and blackberries) versus blended fruit (apple and blackberry smoothie). There are several studies that have reported sex-specific differences in postprandial glycemic response to meal treatments [ 21 , 22 , 23 ]. For this reason, we felt that it was important to include both males and females and to examine sex as a factor in our analysis.…”
Section: Introductionmentioning
confidence: 99%